Price-Earnings Ratio and Stock Returns in the Philippine Stock Market - Valcarcel, Lina J. (Philippine Management Review, 2016)
It has been suggested by some researchers that price-earnings ratio is a good indicator of stock returns and that one good investment strategy is to buy stocks with low price-earnings (P/E) ratios since their performance in terms of stock returns far exceed those stocks with high price-earnings ratios.  Stock returns are computed as the change in the price of the stock from one year to another plus cash dividends during the year.  This study examines whether this is true in the Philippine stock market.  Ninety stocks of listed companies from 1992 to 1995 were taken as sample.  Their price-earnings ratios were computed and the companies were ranked according to their P/E ratios.  Then they were grouped into portfolios of ten stocks each to form nine portfolios, starting with the lowest P/E ratio to the highest. Portfolio 1 contained the stocks with the lowest P/E ratios.  The stock returns of each company from 1992 to 1995 were computed.  From these twenty best performers and twenty worst performers in terms of stocks returns chosen for each year 1992-1995. They were then grouped according to the portfolio to which they belong to determine which portfolio contained the best and worst performers.    Contrary to expectations, Portfolio 1 which contained the lowest P/E ratio stocks contained only three best performers while it had 23 worst performers in that category.  The best performers were observed to belong to Portfolios 6 and 5.  However, the other best performers were scattered among the different portfolios.  This seems to indicate that the best performers can be found almost anywhere.  Caution should be taken when investing to look into the fundamentals of the individual stocks and not to rely only on P/E ratios.  The plausible explanation for this phenomenon is that investors in emerging markets like the Philippines invest in stocks with potential for growth so that investors put their money even in expensive stocks if they see growth potential.  The only constraint to their investment activity is their liquidity.